Investigation of different approaches for exhaled breath and tumor tissue analyses to identify lung cancer biomarkers. Issue 6 (June 2020) - Gashimova, Elina; Temerdashev, Azamat; Porkhanov, Vladimir; Polyakov, Igor; Perunov, Dmitry; Azaryan, Alice; Dmitrieva, Ekaterina
Abstract: Development of early noninvasive methods for lung cancer diagnosis is among the most promising technologies, especially using exhaled breath as an object of analysis. Simple sample collection combined with easy and quick sample preparation, as well as the long-term stability of the samples, make it an ideal choice for routine analysis. The conditions of exhaled breath analysis by preconcentrating volatile organic compounds (VOCs) in sorbent tubes, two-stage thermal desorption and gas-chromatographic determination with flame-ionization detection have been optimized. These conditions were applied to estimate differences in exhaled breath VOC profiles of lung cancer patients and healthy volunteers. The combination of statistical methods was used to evaluate the ability of VOCs and their ratios to classify lung cancer patients and healthy volunteers. The performance of diagnostic models on the test data set was greater than 90 % for both VOC peak areas and their ratios. Some of the exhaled breath samples were analyzed using gas chromatography coupled with mass spectrometry (GC-MS) to identify VOCs present in exhaled breath at lower concentration levels. To confirm the endogenous origin of VOCs found in exhaled breath, GC-MS analysis of tumor tissues was conducted. Some of the VOCs identified in exhaled breath were found in tumor tissues, but their frequency of occurrence was significantly lower than in the case of exhaled breath. Abstract : Analytical chemistry; Biomedical engineering; Cancer research; volatile organic compounds, exhaled breath analysis, tumor tissue analysis, lung cancer, thermal desorption, GC-FID, GC-MS